Effect of Nitrogen fixing Microorganisms and organic manures on the Biomass production of vetiver (Vetiveria zizanioides) - D. Stella, D. Sangeetha (Journal of Phytology, 2009)
Vetiver (Vetiveria Zizaniodies) is a tall tufted, perennial, scented grass with long narrow leaves and an abundant network of roots. Roots are more useful part of the plant. In the present study, the vetiver is grown using garden soil, cowdung, vermicompost with and without the N2 fixing bacteria Azospirillum and Azotobacter. The 120th day results showed that the ideal combination for the growth of vetiver is vermicompost + Azospirillum + Azotobacter. The morphological parameters showed that the maximum root and shoot length, dry weight, number of culms, number of leaves and total chlorophyll were 99.75 cm, 231.00 cm, 2.45 g, 40 culms/plant, 172 leaves/plant and 41.00 mg/g respectively. The antibacterial activity of V. Zizanioides leaves and roots by disc diffusion method showed the maximum zone of inhibition against various pathogenic bacteria. However the root extract showed larger zone of inhibition than leaf extract. It was observed that the maximum zone of inhibition was found to be 32 mm against Staphylococuss aureus and the minimum inhibition was found to be 22 mm against Enterobacter faecalis. These results showed that, the extracts of vetiver are pharmacologically important they may be tested for control of pests and other ailments of human beings.